The Moms' Empowerment Program Addresses Traumatic Stress in Mothers with Preschool-Age Children Experiencing Intimate Partner Violence. Issue 10 (26th November 2019) - Graham-Bermann, Sandra A.; Howell, Kathryn H.; Miller-Graff, Laura E.; Galano, Maria M.; Lilly, Michelle M.; Grogan-Kaylor, Andrew
ABSTRACT: Objective: The Moms' Empowerment Program (MEP) provides affordable services to address the effects of women experiencing intimate partner violence (IPV) and to enhance their mental health. In past evaluations with mothers of school-age children this ten-session program was successful in reducing women's symptoms of posttraumatic stress. Method: A new efficacy trial compares outcomes for women with preschool-age children who received the MEP to those randomly assigned to a waitlist comparison condition. Women with young children ( N = 120) who had experienced IPV living in Southeast Michigan and Ontario, Canada, were assessed at baseline, 5 weeks later (at post-intervention) and at approximately 8-month follow-up. Using standardized measures, this evaluation compared rates of change in women's symptoms of posttraumatic stress. Results: Approximately 46% of the women were diagnosed with posttraumatic stress disorder (PTSD); 94% reported re-experiencing symptoms, 85% physiological arousal symptoms, and 69% avoidance/numbing symptoms. Hierarchical Linear Modeling (HLM) results showed that the MEP was somewhat successful in reducing women's symptoms of posttraumatic stress symptoms. However, the extent of improvement was related to both age and the number of sessions attended during the program. Conclusion: This finding indicates that mothers with young children, who have experienced IPV and who are significantly distressed, may be successfully treated by attending this group intervention designed specifically to address their unique experiences and needs. Clinical impact: High rates of traumatic stress and PTSD are found in women who experience intimate partner violence. A comparison study showed that a 10-session group intervention, the MEP, was success in reducing their traumatic stress.